Differences between self-reported and verified adverse cardiovascular events in a randomised clinical trial. Issue 3 (18th March 2013) - Bolland, Mark J; Barber, Alan; Doughty, Robert N; Grey, Andrew; Gamble, Greg; Reid, Ian R
Abstract : Objectives: In clinical trials, adverse events are usually self-reported but may be adjudicated if serious or of particular interest. After adjudicating cardiovascular events for a 5-year calcium supplement trial, we observed discrepancies between self-reported and verified events. We systematically analysed those differences to assess their importance. Design: Secondary analysis of adverse cardiovascular events in a 5-year, randomised, placebo-controlled trial of calcium supplementation (1 g calcium daily) in 1471 postmenopausal women (mean age 74 years). Setting: Clinical research centre. Methods: The participant's medical records were reviewed for all self-reported myocardial infarctions (MIs) or strokes, and the event independently adjudicated. Cause of death was obtained from hospital records or death certificates. To identify unreported events, the national hospital discharge database was searched and related hospital records were reviewed. Results: 45 women reported 64 MIs, of which 33 (52%) were verified after adjudication. An additional 25 MIs were identified: 1 during adjudication of other events, 21 from the hospital discharge database, 3 from death certificates. 68 women reported 86 strokes of which 50 (58%) were verified. An additional 13 strokes were identified: 7 during adjudication of reported transient ischaemic attacks, 5 from the hospital discharge database, 1 from death certificates. Therefore, 43% of verified MIs and 21% of verified strokes were not reported to investigators. For non-adjudicated discharge codes, 10% of MIs and 22% of strokes were not verified after adjudication. Nineteen per cent of verified MIs and 27% of verified strokes were not identified in discharge coding or death certificates. Neither the event source nor the level of adjudication altered the relationship between treatment allocation and cardiovascular events. Conclusions: When adverse event accuracy is critical, researchers should consider adjudicating self-reported events and hospital discharge codes, and attempt to identify unreported events. Trial registration: Australia New Zealand Clinical Trials registry: ACTRN 012605000242628.